Taxonomic study of the genus Atkinsonia Stainton, 1859 (Lepidoptera, Stathmopodidae) in China, with descriptions of two new species - Wang, Shuxia; Guan, Wei; Sinev, Sergey Yu. (Zootaxa, 2016)
The genus Atkinsonia Stainton, 1859 is reviewed in China. Eight species are recognized, including two new species: A. brevisaccula sp. nov. and A. parignipicta sp. nov.; A. clerodendronella Stainton, 1859 is newly recorded for China; two new combinations and one new synonymy are proposed: A. butalistis (Strand, 1917) comb. nov. from Oedematopoda, A. furcata (Wang, 2008) comb. nov. from Oedematopoda, and Oedematopoda jiyuanica Wang, 2008 syn. nov. of A. swetlanae Sinev, 1988. Photographs of adults and illustrations of genitalia are provided, along with a key to identifying the described Chinese species and a map to show their collecting localities.